Inequality, mobility and segregation : essays in honor of Jacques Silber - Bishop, John A.; Salas, Rafael (Research on economic inequality ;, 2012)
This volume honors the lifetime and continuing contributions of Professor Jacques Silber. The book contains 15 papers, which were presented at the Fourth Meeting of the Society for the Study of Economic Inequality, Catania, Sicily, July 2011. Theoretical topics covered in Volume 20 include measuring segregation, welfare and liberty, the use of influence functions in distributional analysis, and the axiomatic approach to multidimensional inequality. Empirical studies include occupational and residential segregation, regional convergence, impact of variable of equivalence scales on income inequality, earnings and educational inequality and mobility, poverty transitions, and welfare reform. These empirical studies examine a variety of countries and cultures: Afro-Latinos, Italian immigrants, and Indian states as well as the European Union and the United States.